Mapa em Rascunho: linhas para a composição de material didático para a modalidade de Educação Mediada (EMe) - Aguiar, Leidiane Marques de (2022)
This work is linked to the research line: Language: Linguistic, Cultural and Teaching Practices of the Stricto Sensu Postgraduate Program in Arts of the Western Paraná State University (UNIOESTE) and has as its research theme the production of didactic material for the Distance Education modality, in this dissertation called Mediated Education (ME). Considering the importance of this pedagogical instrument in the context of ME, given the asynchrony among this modality actors and the interest in contributing to the Learning process of the Distance Education Center of UNIOESTE (NEaDUNI), which has been in the process of building/experimenting the modality for just over five years, and, for this reason, it lacks relevant studies about the didactic material composition consistent with the mentioned education modality and coherent with its philosophy – Rhizome, and cartography, I highlight a guiding question for this investigation: How to produce didactic material consistent with the ME modality to build new knowledge? This way, I demonstrate the researcher's greatest desire in this academic-scientific work: to build, through theoretical and documentary support, a Map with reference lines addressed to the didactic material composition for the NEaDUNI ME modality. The research is based on the theoretical assumptions of Applied Linguistics, the qualitative type, and the cartographic investigative method. It has as its theoretical contribution, singularly, the contemporary French philosophers Gilles Deleuze and Félix Guattari (2011a; 2011b; 2012a; 2012b; 2012c) and the theoretical physicist Basarab Nicolescu (1999), among other interlocutors. As a result of this research process, I understood that the starting-line question could not be answered with actions point (ready recipe) but only by moving lines, which never get tired of making retakes, detours, and reconstructions with the nomad spirit that is peculiar to knowledge, which is made and remade in multiple contexts. I hope that the map based on six clues (clue 1: line-desiring, clue 2: line-becoming, clue 3: line-cartography, clue 4: line-composition, clue 5: line-experimentation and clue 6: line-passage) and the intertwining of the lines, mapped during the process of conceptual exploration and understanding of the deleuzeguattariana Philosophy of difference, can stimulate the composition of didactic material coherent with the rhizomatic and cartographic philosophy of NEaDUNI and with the need to carry out a transdisciplinary education, transversal, emancipatory and consistent with the present century.